2015
DOI: 10.1111/1556-4029.12721
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Injury Pattern Analysis in a Light Rail Transit Death: A Retrospective Case Study

Abstract: Within the context of medical examiner's offices, forensic anthropologists are increasingly being asked to assist with the interpretation of traumatic skeletal injury. This case study presents an example of trauma analysis performed by forensic anthropologists at the Maricopa County Forensic Science Center in Phoenix, Arizona. The primary goal of this study is to document an uncommon pattern of traumatic injury-severe grinding abrasions of the lower appendage that macroscopically resemble sharp force trauma, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…KEYWORDS: forensic science, forensic anthropology, skeletal trauma, sharp force trauma, dismemberment, reciprocating saws Trauma analysis is considered one of the most crucial aspects of forensic anthropology (1,2) and is typically divided into three main categories: projectile, blunt, or sharp (3). In particular, sharp force trauma encompasses tools used for slicing, stabbing, cutting, hacking, and sawing (3).…”
mentioning
confidence: 99%
“…KEYWORDS: forensic science, forensic anthropology, skeletal trauma, sharp force trauma, dismemberment, reciprocating saws Trauma analysis is considered one of the most crucial aspects of forensic anthropology (1,2) and is typically divided into three main categories: projectile, blunt, or sharp (3). In particular, sharp force trauma encompasses tools used for slicing, stabbing, cutting, hacking, and sawing (3).…”
mentioning
confidence: 99%
“…A case is described where the dragged individual was determined to die on impact (8). Train-related dragging deaths are also described within literature; the distance of dragging in these cases was much longer than typical distances in cases involving automobiles (9, 10). These reports show the variety of circumstances in which dragging and grinding injury-related cases can result in death, and the skin and underlying soft tissue and bone injuries portrayed in each report are very similar to those in the two cases presented here.…”
Section: Discussionmentioning
confidence: 88%
“…Although dragging/grinding injuries are not especially common, several reports exist within the forensic literature (1, 310). Hochmeister et al discuss different positions of being pinned under the automobile and the repercussions of each position of grinding (3).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the decapitations/dismemberment from railway-related suicide are often the subject of discussion when considering the manner of death [ 37 ]. For example, in their study, Kendell et al clarify the manner of death in an unusual case of suicide by Light Rail Transit in which lesions on the deceased’s remains, at a macroscopic level, were similar to those that would be caused by sharp force trauma [ 38 ]. Hanging could result in a complete decapitation as demonstrated in the case described by Dedouit et al The authors showed a case of complete post-hanging decapitation, which underlines the importance of differential diagnosis with post-homicidal decapitation [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…This happens even when the decomposition and dissolution of the other tissues occur, and it is especially useful for distinguishing stab marks made by a serrated and non-serrated blade through the production of a “Y”-shaped or “T”-shaped incision, respectively [ 47 , 48 ]. In the literature, there are several studies that highlighted, in these cases, the importance of anthropological analysis [ 38 ] combined with new methods. Porta et al presented six different cases of dismemberment that occurred in Milano, Italy, between 1999 and 2011, in which, through the macroscopic-morphological analysis of bone lesions (which remains a crucial step in forensic investigations) and microscopic methods, e.g., SEM-EDX (Scanning Electron Microscopy combined with Energy Dispersive X-ray analysis) and stereomicroscopy, it was possible to establish the manner of death and dismemberment and the identification of the tools used in order to distinguish dismemberment and disarticulation and to make a hypothesis about the criminal context [ 5 ].…”
Section: Discussionmentioning
confidence: 99%